Algebraiczne aspekty procesów ekonomicznych - Fałda, Beata; Zając, Józef (Algebraical aspects of economics processes, 2010)
Precise studying of economic processes, with the help of advanced mathematical tools, shows that parameters describing these processes possess their natural algebraic structure. It is important to notice that its recognition guarantee correctness of the analysis and conclu-sions. In this paper the authors construct an algorithm of algebraic procedure, which can be applied in order to classify some basic economic parameters. As a consequence there will be pointed out certain mathematical and probabilistic structures, on the ground of which one may proceed, algebraically correct, calculations of the considered parameters characterizing the economics processes. As an example illustrating the procedure will be presented a direct con-struction of some algebraic structures and the attached types of nonlinear probabilistic spaces
Didactics of Mathematics, 2010, Nr 7 (11), s. 23-32
Keywords: algebraic structures; expected value; means; variance